The Effect Of Recruitment On Employee Performance With Selection As A Moderating Variable - Desri, Syuryatman; Sirait, Evi; Wibowo, Teguh Setiawan; Kusuma, Muhammad Eko Abrian; Ahmadun, Ahmadun (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
ABSTRACT. Good recruitment carried out by a research company is believed to improve company performance because the human resources produced are not haphazard/high quality, are used to not being influenced by the habits of Collusion, Corruption and Nepotism, are educated, and have high integrity. Of course, this must be supported by good selection and must be implemented by a company so that employee performance can be achieved more easily. This research is quantitative research with an explanatory approach. The data in this research was distributed using an online questionnaire method to employees and a number of HRD PT. As many as 200 employees and 100 HRD are spread across Indonesia, all of which contain statements of agree, strongly agree, disagree, strongly disagree and indifferent. This data can also be called primary data. The result in this research show show a positive relationship and a significant influence on employee performance with a value of 0.031 which is smaller than the significance level of 0.05. Thus the first hypothesis and the researcher's first belief are accepted and can be proven. Not too different from the statement above, if a good recruitment process is accompanied by good results, high employee integrity, employee professionalism and the quality of human resources which will ultimately have an impact on employee performance will be easier to obtain. This can be proven by the results of the third table of Path Coefficients in this research which shows a positive relationship and a more significant influence on employee performance because the P-Values value is positive and has a more significant influence, namely 0.000, which is more significant than the direct test of 0.031. Thus the second hypothesis and second belief in this research can be accepted. Keywords: Recruitment, Employee Performance, Selection